Enhanced penetration of exogenous EPCs into brains of APP/PS1 transgenic mice - Yuan, Xiaoyang (Am J Transl Res, 2016)
The aim of this study was to investigate the repair function of exogenous Endothelial progenitor cells (EPCs) for brain microvascular damage of the APP/PS1 transgenic mouse model of Alzheimer’s disease (AD). This study used a density-gradient centrifugation method to isolate mononuclear cells (MNCs) from mouse bone marrow, which were subsequently seeded and cultured. Cells were characterized by morphology and detection of the surface markers CD34 and CD133 at different time points by immunofluorescence (IF) and flow cytometry (FCM). Then, EPCs were transfected with GFP adenoviral vectors (GFP-EPCs). Wild-type (WT) and APP/PS1 transgenic mice both received GFP-EPCs injection through the tail vein, and using a PBS buffer injection as the control. Seven days later, the animals’ brain tissue was isolated. Expression of GFP was detected by quantitative polymerase chain reaction (qPCR) and western-blot (WB), while the fluorescence of GFP within the brains of mice was observed under a fluorescence microscope. Higher mRNA and protein expression of GFP, accompanied with increased green fluorescence, were detected in the brain of GFP-EPCs-injected APP/PS1 mice, as compared with GFP-EPCs-injected WT mice. The results show that the APP/PS1 transgenic mouse model of AD exhibited enhanced penetration of exogenous EPCs into brains than the WT mice.